FACTORS OF INCREASING THE ECONOMIC EFFICIENCY OF SMALL BUSINESS ENTITIES IN AGRICULTURE OF NAMANGAN REGION (American Journal of Business Management, Economics and Banking, 2026)
In this scientific article, on the example of Namangan region, the factors of increasing the economic efficiency of small business entities operating in agriculture – small farms and farmers-are studied on the basis of an agro-economic approach.n this scientific article, on the example of Namangan region, the factors of increasing the economic efficiency of small business entities operating in agriculture – small farms and farmers-are studied on the basis of an agro-economic approach. In the study, the impact of the profitability of smallholdings, the cost–income structure and the mechanisms of financial support provided by the state on the productivity was assessed on the basis of model statistics. The results show that preferential lending, subsidies, modernization of production processes and the development of market infrastructure are important factors in increasing the profitability of small business entities.